2020
DOI: 10.1038/s41467-020-16218-4
|View full text |Cite
|
Sign up to set email alerts
|

Interneuron hypomyelination is associated with cognitive inflexibility in a rat model of schizophrenia

Abstract: Impaired cognitive functioning is a core feature of schizophrenia, and is hypothesized to be due to myelination as well as interneuron defects during adolescent prefrontal cortex (PFC) development. Here we report that in the apomorphine-susceptible (APO-SUS) rat model, which has schizophrenia-like features, a myelination defect occurred specifically in parvalbumin interneurons. The adult rats displayed medial PFC (mPFC)-dependent cognitive inflexibility, and a reduced number of mature oligodendrocytes and myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 70 publications
2
45
1
Order By: Relevance
“…Notably, the synchronization of neuronal ensembles in the gamma range frequency, which largely depends on FSI activity 50 , is commonly altered in this disease. Moreover, a recent study performed in a rat model of schizophrenia showed a hypomyelination of cortical PV + interneurons 51 . Considering our demonstration of the important role of FSI myelination in regulating the function of FSI, it is thus possible that FSI myelination defects alter local cortical circuit oscillations in vivo which, in turn, contribute to cognitive deficits observed in this disease 5,15 .…”
Section: Discussionmentioning
confidence: 98%
“…Notably, the synchronization of neuronal ensembles in the gamma range frequency, which largely depends on FSI activity 50 , is commonly altered in this disease. Moreover, a recent study performed in a rat model of schizophrenia showed a hypomyelination of cortical PV + interneurons 51 . Considering our demonstration of the important role of FSI myelination in regulating the function of FSI, it is thus possible that FSI myelination defects alter local cortical circuit oscillations in vivo which, in turn, contribute to cognitive deficits observed in this disease 5,15 .…”
Section: Discussionmentioning
confidence: 98%
“…About half of the dry weight of the brain is attributable to lipids and about 80% of brain lipids are part of myelin sheaths. In SZ PFC, abnormalities in myelination are evident and decreased PFC myelin content contributes to disease symptomatology 76 , 77 . Furthermore, polyunsaturated fatty acid levels in the blood are correlated with white-matter integrity in frontal regions of the SZ brain 78 , whereas increased LDL levels are associated with white-matter alterations 79 , and white matter, as well as myelin abnormalities in the PFC contribute to cognitive deficits in SZ 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ultrastructural analysis showed that the mitochondrial surface in the mPFC of NAC-treated APO-SUS and APO-UNSUS rats was decreased ( Fig. 2e; Two-way ANOVA interaction F [1,17] NAC treatment improves hypomyelination in APO-SUS mPFC Hypomyelination of mPFC interneurons occurs in APO-SUS rats during adolescence [16]. Oxidative stress is thought to affect the maturation of PFC interneurons in adolescent SZ patients [22].…”
Section: Nac Treatment Alleviates Oxidative Stress In Apo-sus Mpfcmentioning
confidence: 95%